PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN PBL PADA SISWA KELAS IV SEKOLAH DASAR - sulpanri, sulpanri; indrawati, tin; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated because the lessons have not done using innovative model and the learning is still centered on the teacher so that many students are passive and bored to follow the lesson. This resulted in low student learning outcomes and did not meet the predefined learning mastery standard. The purpose of this research is to describe the improvement of science learning with PBL approach in class IV SDN 13 Kecamatan Koto Timur. This research uses qualitative and quantitative approach. The research procedure includes plan, implementation, observation, and reflection. This research was conducted in two cycles and conducted in collaboration between researcher and observer. The techniques used in data collection are observation, PBL approach stages, and tests. The results showed that a) planning cycle I 80.35% and cycle II 96.42%, b) the implementation of the cycle I teacher aspects 76.78% and cycle II 96.42% and student aspects of cycle I 73.21% and cycle II 92.85%, and c) student learning outcomes cycle I with an average of 75.90, and cycle II increased to 83.76. From the results of research conducted can be concluded that by using the approach of PBL can improve student learning outcomes in science learning in grade IV elementary school.  Keywords : IPA; PBL approach